Individual Differences in Sensitivity to Visuomotor Discrepancies - Dewey, John; Mueller, Shane (Frontiers in Psychology, 2019)
This study explored whether sensitivity to visuomotor discrepancies, specifically the ability to detect and respond to loss of control over a moving object, is associated with other psychological traits and abilities. College-aged adults performed a computerized tracking task which involved keeping a cursor centered on a moving target using keyboard controls. On some trials, the cursor became unresponsive to participants’ keypresses. Participants were instructed to immediately press the space bar if they noticed a loss of control. Response times (RT) were measured. Additionally, participants completed a battery of behavioral and questionnaire-based tests with hypothesized relationships to the phenomenology of control, including measures of constructs such as locus of control, impulsiveness, need for cognition, and non-clinical schizotypy. Bivariate correlations between RTs to loss of control and high order cognitive and personality traits were not significant. However, a step-wise regression showed that better performance on the pursuit rotor task predicted faster RTs to loss of control while controlling for age, signal detection, and need for cognition. Results are discussed in relation to multifactorial models of the sense of agency.